Dejavniki tveganja pri bolnikih z ishemično boleznijjo srca - Kvas, Andreja (Obzornik zdravstvene nege, 2000)
There exist many data that show that heart and circulatory system diseases, including ishaemic heart disease, are the leading cause of morbidity and mortality in our country and elsewhere. This is to a terrifying degree due to unfamiliarity with risk factors. The aim of the research study " Familiarity with risk factors" was to find out the extent of the knowledge of risk factorsin patients and healthy clients, the degree to which these risk factorsare taken into account in everyday life and the possible ways to enhance the knowledge about them. It was found out that not enough patient andhealthy clients are familiar with risk factors for ishaemic heart diseases,and therefore do not live their everyday lives according to them. Permanent health education of patients and healthy clients should be organized, and carried out by especially educated health personnel, with the professor of health education occupying the leading position.
Keywords: cardiovascular disease; Coronary disease; Counseling; dejavniki tveganja; Diabetes mellitus; Disease susceptibility; Exercise; Health food; Hypertension; kardiovaskularne bolezni; koronarna bolezen; Mortality; Patient education; Prevention and control; Risk factors; Smoking